2015
DOI: 10.1371/journal.pone.0136205
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin/Tie2 Dysbalance Is Associated with Acute Kidney Injury after Cardiac Surgery Assisted by Cardiopulmonary Bypass

Abstract: IntroductionThe pathophysiology of acute kidney injury (AKI) after cardiac surgery is not completely understood. Recent evidence suggests a pivotal role for the endothelium in AKI. In experimental models of AKI, the endothelial specific receptor Tie2 with its ligands Angiopoietin (Ang) 1 and Ang2 are deranged. This study investigates their status after cardiac surgery, and a possible relation between angiopoietins and AKI.MethodsFrom a cohort of 541 patients that underwent cardiac surgery, blood and urine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…In kidney biopsies of patients who died with AKI in an intensive care unit, the mRNA levels of angiopoietin‐1 were decreased and the angiopoietin‐2/1 ratio was increased immediately post‐mortem . In addition, cardiac surgery with the use of a cardiopulmonary bypass leads to systemic changes in molecules of the angiopoietin balance system, and these changes are more pronounced in patients who develop AKI . In the present study, the level of angiopoietin‐1 in the AKI group with recovery was significantly increased after DHP‐PMX therapy compared to before this therapy.…”
Section: Discussionsupporting
confidence: 41%
“…In kidney biopsies of patients who died with AKI in an intensive care unit, the mRNA levels of angiopoietin‐1 were decreased and the angiopoietin‐2/1 ratio was increased immediately post‐mortem . In addition, cardiac surgery with the use of a cardiopulmonary bypass leads to systemic changes in molecules of the angiopoietin balance system, and these changes are more pronounced in patients who develop AKI . In the present study, the level of angiopoietin‐1 in the AKI group with recovery was significantly increased after DHP‐PMX therapy compared to before this therapy.…”
Section: Discussionsupporting
confidence: 41%
“…Several relatively smaller studies have recently explored associations of endothelial biomarkers and AKI. Recent case-control studies of cardiac surgery patients have found that plasma levels of Ang-2 increase post-surgically by a greater extent in patients who develop AKI than in controls [ 41 , 42 ]. A cross-sectional study of critically ill patients at inception of renal replacement therapy in the ICU found that circulating Ang-2 was correlated with AKI stage and with 28-day mortality risk [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 is supposed to reflect the amount of endothelial activation [32] and to predict the severity and outcome in critically ill patients or of illnesses like acute pancreatitis [32], CKD [15], or after cardiac surgery [33], in early stages of the medical conditions. These predictions were often linked to an deterioration of renal function [15, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…These predictions were often linked to an deterioration of renal function [15, 32, 33]. Taking into account the differences in the present study between serum creatinine/eGFR(crea) and serum cystatin C/eGFR(cys) and the assumption that serum cystatin C or the eGFR(cys) are more sensitive and earlier markers of renal dysfunction or damage [16, 26, 34], one possible conclusion might be that serum cystatin C concentrations, eGFR(cys) and serum Ang-2 concentrations might be reacting sooner towards renal impairment with potential endothelial activation than serum creatinine concentrations.…”
Section: Discussionmentioning
confidence: 99%